Accommodating Bereaved Parents in the Workplace: A Scoping Review. Issue 4 (19th May 2023) - Schoonover, Kimberly L.; Yadav, Hemang; Prokop, Larry; Lapid, Maria I.
Abstract: Helpful workplace support strategies and accommodations (WSSA) for bereaved parents returning to work was assessed via comprehensive search of databases from 1990 to January 21, 2022. Eleven of 45 qualitative articles met inclusion. Bereaved parents often felt returning to work provided a coping strategy for and/or distraction from grief; however, some received insensitive comments by employer/coworkers. Helpful WSSA included flexibility on date to return to work and schedule. In conclusion, due to the intensity of their grief, bereaved parents benefit from a workplace offering individualized time off for bereavement and workplace accommodations to address potential difficulty meeting prior productivity demands.